The Role of Informatics Engineering in the Development of Digital Assets as an Alternative Solution Amid Economic Crisis - Natalia Artha Malau; Jeovano Lorensius Mamesah; Citra Resky Kabolo; Christiany Cheerel Runturambi; Fadel Dasilva Sumaga (Publikasi Indonesia, 2026)
The current economic crisis affecting multiple sectors demands digital technology innovations as effective and efficient alternative solutions. This study examines how informatics engineering can contribute to the development of blockchain-based digital assets, particularly through the utilization of cryptocurrency, NFTs, and the simulation of Central Bank Digital Currency (CBDC). The research adopts an implementation-based approach by developing digital assets through a series of stages, including a literature review, needs analysis, system design, and functional evaluation. The findings show that blockchain-based digital assets can provide secure, transparent, and inclusive solutions as an alternative for economic reinforcement amid crisis conditions. The study implies that strategic collaboration among academics, technology developers, financial institutions, and regulators is essential to create an inclusive, efficient, and sustainable digital asset ecosystem that can contribute to national economic resilience.